Genealogi Kompetensi Pendidik: Dialektika Manajemen Sumber Daya Manusia dalam Ekosistem Madrasah (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze human resource management as a strategic role in developing the competency of madrasah teachers. This study uses a qualitative approach with a descriptive research type at the MA Al-Amiriyyah madrasah. The techniques used for data collection are in-depth interviews, participatory observation, and documentation studies. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this study indicate that the implementation of human resource management functions including planning, recruitment, training, and performance evaluation, have a significant role in improving the pedagogical, professional, and personality competencies of madrasah teachers. In addition, the support of madrasah leadership policies and a conducive work culture are the main supporting factors for the success of developing madrasah teacher competencies. This study concludes that human resource management that is managed strategically and sustainably can improve the quality of madrasah teachers and the quality of education as a whole. Thus, the implementation of strategic human resource management will contribute to the continuous improvement of the quality of madrasah teachers.